Total Knee Arthroplasty for Treatment of Post-Traumatic Arthritis: Systematic Review - Almalki, Meshari Musaad; Alsalmi, Ahmed Atiah; Alsufyani, Emad Ruddah; Ahmad, Tayyab (International Journal of Innovative Research in Medical Science, 2022)
Background: Post traumatic arthritis is one of the most common reasons for joint disability worldwide. The aim of this study was to review and discuss the functional outcomes as well as complications and survivorship related with total knee arthroplasty in the treatment of post traumatic arthritis. Methods: This is a systematic review which was conducted according to the PRISMA guidelines. In this study, we searched several data bases including PubMed, Cochrane Library and SCOPUS for English language clinical research studies whether prospective and retrospective studies in order to examines the use of total knee arthroplasty for the management of post traumatic arthritis. We assessed all relevant articles RESULTS: In this review, we included total of sixteen studies; ten studies were retrospective and six were prospective studies. The pooled results showed an increase in the range of motion and pain reduction after the surgery while the most common complications including infection, stiffness, intraoperative rupture of tendons, wound complications as well as osteolysis. Moreover, comparing the results with patients with osteoarthritis, patients with post traumatic arthritis needed more revisions especially for polyethylene wear. Conclusion: However, the high rate of complications reported with total knee arthroplasty, it is considered an effective treatment for post traumatic arthritis as it found to improve the range of motion and general functional outcomes.